The Role of OSCE and EU Cooperation in Resolving the Russia-Ukraine Conflict - Mahilaj, Sara (European Scientific Journal, ESJ, 2023)
The ongoing conflict between Russia and Ukraine has had significant consequences not only for the two states but also for the international community. The Organization for Security and Cooperation in Europe (OSCE) and the European Union (EU) have played crucial roles in resolving the conflict, with their cooperation being essential for creating a peaceful and stable outcome. This paper aims to analyze the role of OSCE and EU cooperation in resolving the Russia-Ukraine conflict and identify the challenges and areas for improvement in their coordination based on a qualitative approach. The OSCE Special Monitoring Mission to Ukraine (SMM) and the European Union Satellite Centre (SatCen) were particularly instrumental in providing unbiased monitoring and reporting of violations of the ceasefire agreement. Despite the challenges faced in coordinating their efforts, this paper presents that SMM and SatCen have proven to be valuable tools in promoting peace, security, and respect for human rights in the conflict-affected region. Thus, through this paper scholars could use it as a reference to start to study more the SatCen relevance and SMM role, to explain relations between EU and OSCE through their influential tools. The OSCE and EU have been actively engaged in conflict resolution efforts, with a focus on diplomatic and economic sanctions against Russia. In reviewing the OSCE’s cooperation with the EU, this paper suggests that they need to find other ways to minimize their limitations. The lack of political will and agreement among member states has weakened the effectiveness of the OSCE, while the EU’s sanctions policy has been questioned as a means of resolving the conflict. The paper suggests that the OSCE should focus on strengthening its capacity for conflict prevention, management, and resolution as well as monitoring and reporting on violations of human rights. The EU should increase economic assistance to Ukraine and find other ways to cooperate with the OSCE to address human rights concerns and support a peaceful resolution to the conflict. Ultimately, the paper argues that a comprehensive and inclusive approach is needed to effectively address the conflict and promote sustainable peace and stability in the region.